Dimension in the Poetry of Al-Nasser Gharib Allah - Abdul Rahman Mohamed, Eman Al-Tarifi (Tanjong Malim, 2023)
Dimension in the Poetry of Al-Nasser Gharib Allah by Abdul Rahman Mohamed, Eman Al-Tarifi